3‐D electrical resistivity structure based on geomagnetic transfer functions exploring the features of arc magmatism beneath Kyushu, Southwest Japan Arc. Issue 1 (17th January 2017) - Hata, Maki; Uyeshima, Makoto; Handa, Shun; Shimoizumi, Masashi; Tanaka, Yoshikazu; Hashimoto, Takeshi; Kagiyama, Tsuneomi; Utada, Hisashi; Munekane, Hiroshi; Ichiki, Masahiro; Fuji‐ta, Kiyoshi
Abstract: Our 3‐D electrical resistivity model clearly detects particular subsurface features for magmatism associated with subduction of the Philippine Sea Plate (PSP) in three regions: a southern and a northern volcanic region, and a nonvolcanic region on the island of Kyushu. We apply 3‐D inversion analyses for geomagnetic transfer function data of a short‐period band, in combination with results of a previous 3‐D model that was determined by using Network‐Magnetotelluric response function data of a longer‐period band as an initial model in the present inversion to improve resolution at shallow depths; specifically, a two‐stage inversion is used instead of a joint inversion. In contrast to the previous model, the presented model clearly reveals a conductive block on the back‐arc side of Kirishima volcano at shallow depths of ~50 km; the block is associated with hydrothermal fluids and hydrothermal alteration zones related to the formation of epithermal gold deposits. A second feature revealed by the model is another conductive block regarded as upwelling fluids, extending from the upper surface of the PSP in the mantle under Kirishima volcano in the southern volcanic region. Third, a resistive crustal layer, which confines the conductive block in the mantle, is distributed beneath the nonvolcanic region. Fourth, our model reveals a significant resistive block, which extends below the continental Moho at the fore‐arc side of the volcanic front and extends into the nonvolcanic region in central Kyushu. Key Points: 3‐D electrical resistivity model obtained by using two‐stage inversion of two data types Resistivity model shows magmatic variations beneath Kyushu Island Electrical resistivity imaging provides insight into the features of arc magmatism